A critical assessment of John Milbank's Christology - N. Vorster (Acta Theologica)
John Milbank is well known for attempting to develop a participatory theology. This article specifically assesses his Christology. The first section provides a synthetic explication of his Christology by focussing on his notions of participation, paradox, poesis, incarnation, the cross, and ecclesiology. The second section provides a critical assessment. The central argument is that Milbank’s Christology is inadequate in a participatory sense, because it lacks particularity and personal relationality. This inadequacy is probably due to the way in which he fuses Neo-Platonism and postmodern lingualism in order to construct his ontology. In order to maintain his non-violent and poetic ontological position, Milbank needs to revert to a general, “high” and impersonal Christology, and disregard “low” Christology. However, if one’s ontological construction leads to a detached Christology, which does not adequately affirm the central notion of one’s theology, serious doubts arise concerning the legitimacy of one’s method.